Consumed capacity monitoring of Sandvik MD and MDX bolts using ultrasonic pulse echo - Vallati, O; Wang, J; Young, P (Caving 2026: Sixth International Conference on Block and Sublevel Caving, 2026)
Rockbolt degradation poses a major challenge in caving operations as dynamic stresses and progressive deformation reduce reinforcement capacity. Recent studies, including MRIWA GSSO2, have identified the lack of low-cost, reliable instrumentation for measuring bolt elongation as a critical gap in effective ground support management. To address this limitation, Sandvik introduces xCell Banshee, an innovative monitoring approach that integrates ultrasonic pulse echo technology into every MD and MDX bolt manufactured by Sandvik, enabling non-destructive, in situ measurement of bolt length, elongation, and consumed capacity. This universal implementation ensures that ground support monitoring becomes a standard feature across MD and MDX bolts, setting a new benchmark for safety and performance in underground mining. Importantly, the system is designed to be largely deployable and truly scalable on site, enabling mine-wide instrumentation without specialised installation procedures or additional hardware. The paper first reviews current practices in caving operations for assessing rockbolt capacity and their limitations. It then introduces xCell Banshee, the new technology, explaining the underlying measurement principles, and details the laboratory testing program undertaken to validate the approach. Laboratory investigations assessed measurement accuracy under varying loading conditions. Tests conducted on 2.4 and 3 m bolts demonstrate robust signal performance and strong agreement between ultrasonic measurements and mechanically measured elongation. Calibration trials identified a systematic length correction factor and quantified temperature effects, leading to the development of compensation algorithms suitable for field application. The xCell Banshee system represents a significant advancement in ground support monitoring by providing real-time, non-destructive assessment of rockbolt integrity and deformation. Integration with digital monitoring platforms enables predictive maintenance strategies and has the potential to significantly enhance safety and performance in caving operations.
Keywords: MD; MDX; rockbolt; ground support; monitoring; capacity